Vitiligo-Like Secundary to Ribociclib: A Case Report - Marquez Maldonado, Carol Estefania; Larios Rojas, Alan; Achell Nava, Lucia; Arellano Vivero, Dolores Maribel; Maldonado Colin, Guadalupe; Loredo Alanis, María Azalea; Bencomo Loepky, Samuel (International Journal of Medical Science and Clinical Research Studies, 2025)
Ribociclib, a cyclin-dependent kinase (CDK) 4/6 inhibitor, is widely used in the treatment of metastatic breast cancer. However, its dermatologic adverse effects, particularly vitiligo-like lesions, have been recently reported. The pathomechanisms underlying these lesions remain unclear, but immune-mediated melanocyte destruction has been proposed. A literature review reveals an increasing number of similar cases, highlighting the need for further investigation into these adverse effects’ incidence, mechanisms, and clinical implications. We present a case of vitiligo-like depigmentation in a patient undergoing ribociclib therapy.